Variação espacial da resistividade elétrica em terraços agrícolas: correlação estatística entre TRE e algoritmos de direção de fluxos = Electrical resistivity spatial variation in agriculture terraces : statistical correlation with ERT and flow direction algorithms - Fernandes, Joana (2018)
The construction of terraces, in the Douro Region, with earthen embankments rises aset of problems related to the hydrological processes. The main objective of this study is the evaluation of the electrical resistivity spatial variation in agriculture terraces atDouro valley (Portugal).To achieve this objective two variables are analysed, the soil electrical resistivity andthe flow direction algorithms. In field survey, 13 electrical resistivity profiles wererecorded. The contributing area calculated with the algorithms D (DeterminiscInfinity Flow) and MFD (Multiple Flow Direction), are the base of the internal runoffmodelling, both supported by the digital elevation model with a special resolution of1m2.Was stablished a correlation between the spatial variation of the soil electrical resistivityrepresented by standard deviation electrical resistivity of each profile and the averagevalue of contributing area coincident with each profile.The electrical resistivity standard deviation seems to be moderately good correlated forthe D algorithm at about 1m of depth and has a good correlaon at 1,5m to 2m ofdepth with the MFD algorithm. The results analysis shows a significant positivestatistical correlation between electrical resistivity standard deviation and thecontributing areas (MFD and D) depending on the soil depths.